2002
DOI: 10.1038/sj.jhh.1001399
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of blood pressure and prevalence of hypertension in Tehran adult population: Tehran Lipid and Glucose Study (TLGS), 1999–2000

Abstract: The purpose of this study was to estimate the current prevalence and distribution of hypertension in an adult Tehranian population. Data were collected for 3343 men and 5148 women aged 20-69 years in the Tehran Lipid and Glucose Study (TLGS), which is a cross-sectional phase of a large epidemiologic study, first established in 1999. The study used the mean of two separate blood pressure (BP) measurements in each individual. Twenty-two percent (23% of women vs 20% of men, P = 0.01) had hypertension according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 19 publications
7
52
0
Order By: Relevance
“…Blood pressure was measured twice after the participants sat for 15 min (26). Additional covariate information regarding age, smoking habits (27), physical activity (28), medical history, and current use of medication (29) was obtained using validated questionnaires completed during the screening and every month as reported earlier.…”
Section: Measurementsmentioning
confidence: 99%
“…Blood pressure was measured twice after the participants sat for 15 min (26). Additional covariate information regarding age, smoking habits (27), physical activity (28), medical history, and current use of medication (29) was obtained using validated questionnaires completed during the screening and every month as reported earlier.…”
Section: Measurementsmentioning
confidence: 99%
“…Inter-and intra-assay coefficients of variation were 2 and 0.5% for TC and 1.6 and 0.6% for TG, respectively. Blood pressure was measured twice after the participants sat for 15 min (Azizi et al, 2002b). Additional covariate information regarding age, smoking habits (Azizi et al, 2003c), physical activity (Mirmiran et al, 2003), medical history and current use of medications (Azizi et al, 2003c) was obtained using validated questionnaires, as reported earlier.…”
Section: Assessment Of Other Variablesmentioning
confidence: 99%
“…33 Blood pressure was measured twice after the participants sat for 15 min. 2 Additional covariate information regarding age, smoking habits, 33 physical activity, 34 medical history and current use of medications 3 was obtained using validated questionnaires, as reported earlier.…”
Section: Assessment Of Other Variablesmentioning
confidence: 99%
“…1 The risk of cardiovascular disease, the prevalence of which continues to rise in Iran, 2 increases with the occurrence of metabolic syndrome. 1 A recent study showed that over 30% of Tehranian adults have metabolic syndrome, 3 which is higher than that reported from USA.…”
Section: Introductionmentioning
confidence: 99%